Notice: Payments for answers will end 4/10/2017. Click for more info.
You have new items in your feed. Click to view.
Question and answer
Q: Please help me with checking my answers. Simplify by using the Distributive Property: 4a + 5(b – 2)
A: 4a + 5(b – 2) = 4a + 5b - 10
Get an answer
Original conversation
User: Please help me with checking my answers. Simplify by using the Distributive Property: 4a + 5(b – 2)

Weegy: 4a + 5(b – 2) = 4a + 5b - 10
lechatelier|Points 66|

User: Please help me with checking my answers. Simplify by using the Distributive Property: 8(3a + 2b – 5c)

Weegy: Solution : 8(3a + 2b – 5c) = 24a + 16b - 40c
Expert answered|bongche|Points 1319|

User: Please help me check my answers. Simplify by Combining Like Terms: 14xy^3 – 22xy^3 + 5xy^3

Weegy: Solution : 14xy^3 – 22xy^3 + 5xy^3 by combining like terms 14xy^3 – 22xy^3 + 5xy^3 = -3xy^3
Expert answered|bongche|Points 1319|

User: Applying PEMDAS, simplify these expressions: 6 + 4(3^2) – 20

Weegy: Solution : Applying the PEMDAS 6 + 4(3^2) – 20 6 + 4(3^2) – 20 = 6 + 4 (9) - 20 ; = 6 + 36 - 20 = 42 - 20 = 22
Expert answered|bongche|Points 1319|

User: Applying PEMDAS, simplify: -12 – 48 ÷ 6 x 3^2 + 10

Weegy: Solution : -12 – 48 ÷ 6 x 3^2 + 10 = -12 – 48 ÷ 6 x 9 + 10 = -12 – 8 x 3^2 + 10 = -12 – 8 x 9 + 10 = -12 – 72 + 10 = -12 – 62 = -74
Expert answered|bongche|Points 1319|

User: Simplify the espressions with grouping symbols: 14 – [ 3 + (8 – 2)]

Weegy: Solution : 14 – [ 3 + (8 – 2)] = 14 – [ 3 + 8 – 2] = 14 – 3 - 8 + 2 = 5
Expert answered|bongche|Points 1319|

User: Evaluate the expression: Given 4x – 12, evaluate when x = -7

User: Given 3x^2 + 2x – y, evaluate when x = -3 and y = 9

Question
Asked 3/22/2012 8:13:11 PM
Updated 7/16/2014 11:40:23 AM
2 Answers/Comments
This answer has been confirmed as correct and helpful.
Edited by andrewpallarca [7/16/2014 11:38:13 AM], Confirmed by andrewpallarca [7/16/2014 11:40:23 AM]
New answers
Rating
3
4x – 12, x = -7

= 4(-7) - 12
= -28 - 12
= -40
Added 7/16/2014 11:39:09 AM
This answer has been confirmed as correct and helpful.
3
3x^2 + 2x – y, x = -3 and y = 9

3(-3)^2 + 2(-3) - 9
= 3(9) - 6 - 9
= 27 - 6 - 9
= 12
Added 7/16/2014 11:40:22 AM
This answer has been confirmed as correct and helpful.
Comments

There are no comments.

Add an answer or comment
Log in or sign up first.
Questions asked by the same visitor
Please help me. I'm checking my answers. Evaluate the expression: Given 4x – 12, evaluate when x = -7
Weegy: 4x – 12, when x = -7 is the same thing as 4(-7) - 12, which equals -40. Your answer is -40. (More)
Question
Expert Answered
Updated 2/21/2014 11:49:10 AM
0 Answers/Comments
27,012,799 questions answered
*
Get answers from Weegy and a team of really smart lives experts.
S
L
Points 256 [Total 274] Ratings 0 Comments 186 Invitations 7 Offline
S
L
R
Points 145 [Total 296] Ratings 1 Comments 5 Invitations 13 Offline
S
L
Points 130 [Total 130] Ratings 0 Comments 130 Invitations 0 Offline
S
R
L
R
P
R
P
R
Points 66 [Total 734] Ratings 0 Comments 6 Invitations 6 Offline
S
1
L
L
P
R
P
L
P
P
R
P
R
P
R
P
P
Points 62 [Total 13329] Ratings 0 Comments 62 Invitations 0 Offline
S
L
1
R
Points 34 [Total 1450] Ratings 2 Comments 14 Invitations 0 Offline
S
L
Points 10 [Total 187] Ratings 0 Comments 0 Invitations 1 Offline
S
Points 10 [Total 13] Ratings 0 Comments 10 Invitations 0 Offline
S
Points 10 [Total 10] Ratings 0 Comments 0 Invitations 1 Offline
S
Points 2 [Total 2] Ratings 0 Comments 2 Invitations 0 Offline
* Excludes moderators and previous
winners (Include)
Home | Contact | Blog | About | Terms | Privacy | © Purple Inc.